Application of Allometric Equation for Estimating Above-Ground Biomass and Carbon Stock of Urban Trees in Selected Areas of Southern Bénin (West Africa) - Ibrahim, Adekanmbi Dende; Moussahoudou, Issa; Gontran, Dansou Bignon (International Journal of Forest, Animal and Fisheries Research, 2022)
Urban trees play a crucial role and natural role in sequestrating carbon from the atmosphere. This study estimates the above ground biomass, carbon stock and carbon dioxide equivalent of urban trees in southern part of Benin Republic. A complete enumeration of street trees was carried out from which 1119 trees were observed and measured for total height and diameter at breast height. Above ground biomass and carbon stock of trees were estimated using allometric equation, because tree carbon stocks are generally not measured directly whenever the biomass estimation involves rare tree species or trees that are meant for protective and aesthetic purposes. The results of the analysis indicated that the total above ground biomass, carbon stock and carbon dioxide equivalent were 1306.097mt, 613.883mt and 2250.647mt respectively. All trees encountered during data collection belonged to Casuarinaceae, Combretaceae Fabaceae, Myrtaceae, Sterculiaceae, Verbenaceae and Meliaceae families and they comprised eleven different tree species with Khaya senegalensis as the dominant tree species. It can be concluded from this study that the urban trees in southern part of Benin act as a reservoir of atmospheric carbon dioxide and further play important part in the global climate change mitigation.